2022
DOI: 10.1155/2022/9701938
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, Chemical Composition, and Protective Effect of Essential Oil from Chimonanthus nitens Oliv. Leaves on Dextran Sodium Sulfate-Induced Colitis in Mice

Abstract: In this study, the essential oil (EO) was extracted by steam distillation from Chimonanthus nitens Oliv, and the extraction process was optimized by response surface methodology. The optimum process conditions are as follows: extraction time of 4.57 h, soaking time of 1.33 h, and solid-liquid ratio of 1 : 21.4. Under these conditions, the theoretical yield of EO is 1.5624%. The EO compounds were analyzed by gas chromatography-mass spectrometry (GC-MS). A total of 52 chemical components were detected, among whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Essential oils from Chimonanthus nitens Oliv. leaves and Agastache mexicana produced comparable outcomes when administered at equivalent or higher dosages compared to our prescribed dosages of PSEO. , …”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Essential oils from Chimonanthus nitens Oliv. leaves and Agastache mexicana produced comparable outcomes when administered at equivalent or higher dosages compared to our prescribed dosages of PSEO. , …”
Section: Discussionmentioning
confidence: 62%
“…leaves and Agastache mexicana produced comparable outcomes when administered at equivalent or higher dosages compared to our prescribed dosages of PSEO. 52,53 DSS treatment could induce UC by disrupting the intestinal mucosal barrier and then triggering inflammation in the intestinal epithelial cells. Prolonged intestinal inflammation leads to fibrosis, thickening of the intestinal wall, colon degeneration, shortening, and neutrophil infiltration, ultimately culminating in the destruction of crypts and goblet cells.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical investigations in Chimonanthus revealed that these plants have high content of flavonoids (such as quercetin, kaempferol, rutin, hyperin, isoquercitrin, afzelin, etc. ), coumarins and terpenoids [such as 21.43% 3-(4,8-dimethylnona-3,7-dienyl)-furan, 10.51% longifolenaldehyde, 11.85% (+)-2-bornanone, 5.69% Δ-cadinene of Chimonanthus nitens ], while with low yield of bioactive alkaloids ( Shu et al., 2019 ; He et al., 2022 ; Chen et al., 2023 ). The results of this study matched well with the chemical investigations of Chimonanthus plants, and the nine active compounds isolated from C. grammatus included three flavonoids (47, 62, 68), three terpenoids (1, 67, 79), one coumarin (40), steroid (53) and organic acid (31).…”
Section: Resultsmentioning
confidence: 99%
“…5,6 In addition, the volatile components are the key bioactive material basis. 7,8 However, in the granule preparation process, volatile oil is extracted separately and then sprayed on the granule directly. Moreover, no research has been reported on the chemical components of the granule.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the chemical constituents of the leaf demonstrates that coumarins and flavonoids are its main constituents 5,6 . In addition, the volatile components are the key bioactive material basis 7,8 . However, in the granule preparation process, volatile oil is extracted separately and then sprayed on the granule directly.…”
Section: Introductionmentioning
confidence: 99%